Four-Year Outcomes of Left Main Percutaneous Coronary Intervention with a Bioresorbable Scaffold in the Circumflex Ostium - Andrejs Erglis; Inga Narbute; Dace Sondore; Sanda Jegere; Indulis Kumsars; Andis Dombrovskis; Karlis Grikis; Ieva Briede; Kristine Dombrovska; Karlis Trusinskis; Alona Grave; Martins Erglis; et al. (Journal of Interventional Cardiology, 2022)
Objectives. The study aimed to investigate the long-term outcomes of a double stent scaffold strategy in patients with left main (LM) bifurcation lesions involving the ostium of the left circumflex artery (LCX), utilizing a drug-eluting stent (DES) in the LM extending into the left anterior descending artery (LAD) and a bioresorbable vascular scaffold (BVS) in the LCX ostium. Background. The high occurrence of in-stent restenosis of the LCX ostium is the major limitation of percutaneous coronary intervention (PCI) for LM lesions with a two-stent strategy. Methods. This was a single-center, prospective, single-arm study of 46 consecutively enrolled patients with a stable coronary artery disease and significant unprotected LM distal bifurcation disease. Patients underwent imaging-guided PCI using DES in the LM-LAD and BVS in the LCX using a T-stent or mini-crush technique. The primary outcome at four years was the composite of death, myocardial infarction, stroke, and target lesion revascularization (TLR). Results. At four years, the primary outcome was identified in 9 patients (19.6%). All events were TLRs except one myocardial infarction due to BVS thrombosis. Seven of the eight TLRs were a result of side branch BVS restenosis. Univariate predictors of the 4-year outcome were higher LDL cholesterol and BVS size ≤2.5 mm. On multivariate analysis, LCX lesion preparation with a cutting balloon and post-procedure use of intravascular ultrasound for optimization were found to be independent protective factors of MACE. Conclusions. In selected patients with LM distal bifurcation disease, an imaging-guided double stent scaffold strategy with DES in the LM and BVS in the LCX ostium was technically successful in all patients and was reasonably safe and effective for four years.